Paul Maylam, Rhodes University, 1904-2016: An Intellectual, Political and Cultural History (Historia, 2021)
Rhodes University, 1904-2016: an intellectual, political and cultural history researched and written by Rhodes University history professor, Paul Maylam, is an insightful and revealing book. The book covers different themes in the history of this institutionduring which aspects of the intellectual, political and cultural history of Rhodes University is unravelled. This account of the history of Rhodes University is however not an ‘objective’ version told by a neutral impartial observer. This is because Maylam hasbeen associated with this university for almost thirty years. During 1967-1970, he was a student at Rhodes. From 1991 – 2012 he acted as head of the History department and from there he spent four years in retirement working on this book.
Keywords: Rhodes University; Paul Maylam; history; Rhodes University College